Subcutaneous Sarcoidosis - Sarkar J N; Sengupta B; Ganguli S B; Kalra S (Wolters Kluwer Medknow Publications, 1998)
Subcutaneous sarcoidosis in the trunk and proximal extremities in a 52 year old man is reported due to its rarity in the literature. The clinical diagnosis was confirmed by different parameters including histopathology, as well as by exclusion method. The patient was put on 40 mg prednisolone per day for two weeks when the lesions subsided dramatically.